Teaching Community Archiving - Kuecker, Elliott; Beattie, Callie; Bee, Penny; Conley, Madeline; Gillespie, Simone; Hollis, Sophie; Norwood, Alona; Ostrander, Cassilyn; Southern, Hannah; Steitz, Margaret; Wang, Lingyu (Archivaria)

(untitled) (Association of Canadian Archivists, 2024)
Community archiving is grounded in grassroots documentation projects. This article, collectively written by an instructor and students of a community archiving course in a professional ischool, describes a process of teaching community archiving in ways that draw on and embrace community archiving principles and ethos rather than operating in opposition to them. It argues that teaching community archiving can create a classroom community that becomes a community archive in itself, and this article acts as one artifact created in the overall process. The article also offers information on the course outline, outcomes, pedagogical approach, and projects – some of which are documented in the text – that may be useful to other archival educators. It emphasizes the value of the personal, affective, and collaborative aspects of archival practice that are emphasized in community archiving practice and literature, and it also draws attention to the ways in which these operate as dimensions of pedagogy and classroom community, allowing both the content and delivery of the class to work in harmony.